Examining the Relationship Between Conspiracy Theories, Paranormal Beliefs, and Pseudoscience Acceptance Among a University Population - Lobato, Emilio; Mendoza, Jorge; Sims, Valerie; Chin, Matthew (Applied cognitive psychology, 2014)
Summary Very little research has investigated whether believing in paranormal, conspiracy, and pseudoscientific claims are related, even though they share the property of having no epistemic warrant. The present study investigated the association between these categories of epistemically unwarranted beliefs. Results revealed moderate to strong positive correlations between the three categories of epistemically unwarranted beliefs, suggesting that believers in one type tended to also endorse other types. In addition, one individual difference measure, looking at differences in endorsing ontological confusions, was found to be predictive of both paranormal and conspiracy beliefs. Understanding the relationship between peoples' beliefs in these types of claims has theoretical implications for research into why individuals believe empirically unsubstantiated claims. Copyright © 2014 John Wiley & Sons, Ltd.